On some blattisociid mites (Acari: Mesostigmata: Lasioseius, Cheiroseius) from Slovakia, with notes on the genus Hyattella sensu Krantz, 1962 - Mašán, Peter (Zootaxa, 2023)
A new mite species of the Blattisociidae, Lasioseius cheiroseioides sp. nov., is described on the basis of females found in association with the galleries of the longhorned beetle Cerambyx cerdo Linnaeus in old oaks (Quercus sp.) in southwestern Slovakia. The species is unusual in the genus in that it has modified macrosetae on the tarsi II‒IV, a feature considered typical of Hyattella Krantz, 1962, a genus now considered synonymous with Lasioseius Berlese, 1916. Furthermore, Hyattella Krantz, 1962 is a junior homonym of Hyattella Lendenfeld, 1888 (Porifera). Some amendments were made to the original description of Lasioseius epicrioides (Krantz, 1962), the type species of Hyattella, and of Lasioseius lacunosus Westerboer, 1963, which was first reported from Slovakia and is closely related to the new species of Lasioseius. The following new synonymies are proposed: Lasioseius zerconoides Willmann, 1954 = Lasioseius ometes (Oudemans, 1903) and Lasioseius minor Kalúz, 2009 = Lasioseius diffindatus Christian & Karg, 2006. Another blattisociid mite, Cheiroseius arboricola sp. nov., is introduced as a new species. Mašán (2023a) described this species but did not indicate where the holotype is deposited, so its name is not available from that date.